The financial benefits of eLearning - Mark Nichols (Flexible Learning Association of New Zealand, 2012)
In the pioneering days of eLeaming, many institutions suffered from significant levels of investment in eLearning initiatives that brought poor returns. Increasingly, eLeaming projects are required to justify the budgets they request from decision-makers. However, the benefits of eLearning in tertiary education tend to be less quantitatively obvious than the financial gains that corporate training through eLeaming can realise. This paper examines the issues faced by tertiary educators when comparing their eLeaming activities with those of corporate trainers, and suggests ways in which specific Learning projects, both courses and elements within courses, might be justified using CBA (cost-benefit analysis) and ROI(return on investment). The approach suggests ways in which the financially intangible aspects of improved learning and institutional reputation might be considered when justifying eLeaming expenditure.